Psychosocial Problems of War-Affected Youth in Northern Uganda: A Qualitative Study - Stichick Betancourt, Theresa; Speelman, Liesbeth; Onyango, Grace; Bolton, Paul (Transcultural psychiatry, 2009)
Multiple studies have found that children from a variety of cultures who have been affected by war are at increased risk for a range of psychosocial problems. However, most studies are based on Western concepts and assume that these are locally applicable. Very few have investigated how psychosocial problems are perceived by the affected communities, families and the young people themselves. Understanding local perceptions is important to ensuring that local priorities are addressed, and addressed in ways that are likely to be acceptable and effective. In this study we used a previously developed rapid ethnographic assessment method to explore local perceptions of psychosocial problems among issues among children and adults from the Acholi ethnic group that have been displaced by the war in northern Uganda. We conducted 45 free list interviews (N= 30 10-17 year olds, N=15 adults) and 57 key informant interviews (N=32 10-17 year olds, N=25 adults) Our purpose was twofold: 1) To test whether this rapid ethnographic assessment approach previously used among adults would be suitable for use with children; and 2) To use this approach to understand the psychosocial problems affecting local children from their own viewpoint and that of their caretakers, in order to inform subsequent assessment and intervention efforts by organizations serving this population. The rapid assessment approach appears to have worked well for interviewing caretakers and children aged 10-17 years. Several locally defined syndromes were described: two tam/par/kumu (depression and dysthymia-like syndromes), ma lwor (an anxiety-like syndrome), and a category of conduct problems referred to as kwo maraco/gin lugero. The descriptions of these local syndromes are similar to Western mood, anxiety and conduct disorders, but contain some culturespecific elements.
Keywords: War; Children and adolescents; Northern Uganda; Mental health; Qualitative research